Learning Management by Assistant Teachers in State Elementary School - Prihartini, Yogia; Musyaddad, Kholid; Buska, Wahyudi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to determine learning planning, implementation of learning and evaluation of learning carried out by Assisting Teachers at State Elementary School 73, Muaro Jambi Regency. Qualitative research methods. The research was conducted at the State Elementary School 73, Muaro Jambi Regency. To collect data, observations and interviews were carried out as well as documentation. The data collected in this study were then analyzed in three stages as suggested by Miles and Huberman (1992) and Nasution (1988) that in this study there are three stages of analysis in the form of water flow, namely data reduction, data presentation and data conclusion/verification. The results of the research findings indicate that the learning carried out by auxiliary teachers does not meet the pedagogic competencies that professional teachers must possess. This can be seen from several aspects. First, from the aspect of learning planning, there are still assistant teachers who have not designed their own lesson plans. Second, in terms of the implementation of learning, assistive teachers have not used varied methods in learning, they tend to focus on one method, namely the lecture method. Third, from the aspect of learning evaluation, the assistant teacher has not designed learning evaluation questions properly.